Sporadic Creutzfeldt–Jakob disease in two adolescents. Issue 1 (23rd May 2007) - Murray, K; Ritchie, D L; Bruce, M; Young, C A; Doran, M; Ironside, J W; Will, R G
Abstract : Background: Sporadic Creutzfeldt–Jakob disease (CJD) is a condition predominantly affecting older age groups, with cases aged less than 45 years rare and an age at onset or death of less than 20 years exceptional. Methods: Data from the systematic study of sporadic CJD in the UK are available from 1970 onwards. Clinical and pathological data are reviewed in order to identify atypical cases, including those at the extremes of the age range of sporadic CJD. Detailed analysis of atypical cases is undertaken, and in selected cases laboratory transmission studies are carried out in order to provide information on the characteristics of the infectious agent. Results: In the UK, two cases of sporadic CJD in adolescents have been identified, dying at ages 16 and 20 years. The first case predated the epidemic of bovine spongiform encephalopathy and the characteristics of the second case, including laboratory transmission studies, are consistent with a diagnosis of sporadic rather than variant CJD. Conclusion: The cases in this report indicate that sporadic CJD can develop at a very young age, that variant CJD is not the only form of CJD occurring in this age group and that neuropathological examination is essential for accurate diagnosis of human prion disease.